O papel da educação musical no ensino médio técnico integrado do IFAM : perspectivas de docentes e discentes Manaus 2019 - Almeida, Daniele Silva de (2019)
This study has as its theme the importance of music education in three IFAM campuses. The motivation to research this theme came from a concern about why music education is in a space that is strictly focused on technical and professional education. The objective of this work was to understand the role of Music teaching in the academic formation of the Technical High School student of the Integrated Way in the context of the campuses of the Federal Institute of Amazonas; to analyze, according to the perspective of Art / Music teachers and technical high school students of the integrated form of the campuses of Manaus / Am, the function and necessity of the existence of the teaching of Music in these institutions; and make a comparative between the answers of teachers and students. The problem that guided this research was what is the role of musical education in IFAM? For the theoretical basis, a specific literature review was done that involved the areas of History of Music teaching in Brazil, Musical Cognition and Philosophy of Musical Education. The participants of this research were three Art / Music teachers and 218 students of IFAM technical high school, belonging to the three campuses of Manaus of the Institute. The instrument of data collection was a questionnaire divided into two parts, through which the participants give their opinion about what they thought about the subject. It is concluded here that teachers believe that the teaching of music in school is important for different reasons and that they do not reach a consensus, while the students also think that teaching is important, however, most of them justify their answer to the question of well-being and not for musical development purposes.